Therapeutic benefits of quercetin in traumatic brain injury model exposed to cigarette smoke - Faleh Alqahtani; Yousif S. Mohamed Ali; Mohammed M. Almutairi; Abdullah F. Alotaibi; Imran Imran; Musaad A Alshammari; Abdullah K. Alshememry; Shakir D. AlSharari; Thamer H. Albekairi (Elsevier, 2024)
Scientific evidences reported the deleterious effect of cigarette smoking or passive smoking on brain health particularly cognitive functions, blood-brain barrier (BBB) permeability, up-regulation of inflammatory cascades, and depletion of the antioxidant system. These combined effects become more progressive in the events of stroke, traumatic brain injury (TBI), and many other neurodegenerative diseases. In the current study, we investigated the long-term administered therapeutic potential of quercetin in ameliorating the deleterious neurobiological consequences of chronic tobacco smoke exposure in TBI mice. After exposure to 21 days of cigarette smoke and treatment with 50 mg/kg of quercetin, C57BL/6 mice were challenged for the induction of TBI by the weight drop method. Subsequently, a battery of behavioral tests and immunohistochemical analyses revealed the beneficial effect of quercetin on the locomotive and cognitive function of TBI + smoked group mice (p < 0.05 vs control sham). Immunohistochemistry analysis (Nrf2, HO-1, NFkB, caspase 3) demonstrated a marked protection after 21 days of quercetin treatment in the chronic tobacco smoking group possibly by up-regulation of antioxidant pathways, and decreased apoptosis. In conclusion, our findings support the therapeutic effectiveness of quercetin in partly protecting the central neurological functions that become aberrantly impaired in combined habitual cigarette-smoking individuals impacted with TBI.